AARON BUSHNELL'S SUICIDE MESSAGE TO THE WORLD - Bahrun Mahabi (Institut Agama Islam Negeri Ponorogo, 2024)
Abstract: The conflict in Israel and Palestine has led to many demonstrations and protests from all circles around the world. The demonstrations and protests at a later stage developed into quite extreme actions, such as the suicide video by burning the body by Aaron Bushnell which had shocked the world of social media. This research uses a message content analysis method with a conventional approach. Taking data sources from the Twitter/X social media of one of the journalists in America, the researcher's focus is to present the world's reaction data based on the theory of mass communication effects caused by the content of Aaron Bushnell's message who committed the extreme protest action by suicide. The result of this research is that Aaron Bushnell's suicide succeeded in giving affective and conative effects on the world, so that the core content of the message conveyed by Aaron Bushnell in the form of Palestinian liberation can have an impact on the world.